STATUS AND BIOLOGICAL CHARACTERISTICS OF NATURAL REPRODUCTION OF WALNUT FORESTS IN WESTERN TIEN-SHAN (Conferencea, 2022)
Walnut forest is a valuable gene pool of walnut, unique in the world. These walnut forests are located at an altitude of 1000-2000 m above sea level. Natural walnut forests from Central Asia are of great importance in water storage and regulation, preventing soil erosion. The walnut groves growing in the basins of the mountain rivers provide water supply to the irrigated plantations of the mountains and the oases at the same time. The analysis shows that deep scientific studies have not been conducted on the formation of walnut forests and their natural reproduction in Uzbekistan, and we have set the task of carrying out scientific work in this direction.